Legal Pluralism, Customary Law and Human Rights in Francophone African Countries - Frémont, Jacques (Victoria University of Wellington Law Review, 2009)
This article provides a perspective on human rights in sub-Saharan Africa, with an emphasis on states colonised and influenced by the continental cultures of France and Belgium. The author examines what the Pacific can gain from the Francophone countries’ understanding of human rights, with insights into the interface of cultures in post-colonial statehood. The article is one of four background papers which provide paradigms and challenges for a possible Pacific charter.